Android Tablets Made Simple For Motorola XOOM, Samsung Galaxy Tab, Asus, Toshiba and Other Tablets - Karch, Marziah; Made Simple Learning, MSL (Apress : Imprint: Apress, 2011)
If you thought your phone was smart, you should see the new Android tablets! Based on Android 3 Honeycomb, these tablets provide all the computing power you'll need on a device light enough to carry wherever you go. Get the most out of your Android 3.0 Honeycomb tablet with Android Tablets Made Simple-learn all the key features, understand what's new, and utilize dozens of time-saving tips and tricks. Android Tablets Made Simple includes over 500 pages of easy-to-read instructions and over 1,000 carefully annotated screen shots to guide you to Android tablet mastery. You'll never be left wondering, "How did they do that?" This book guides you through: Finding and purchasing the right Android tablet Understanding the Android Honeycomb interface Downloading and using tablet apps.